2019
DOI: 10.1177/0255761418821165
|View full text |Cite
|
Sign up to set email alerts
|

Exploring post-degree employment of recent music alumni

Abstract: The purpose of this research was to identify the various types of employment held by music alumni at one university. We also compare the perceptions of alumni who currently work primarily in music with those of alumni who work outside the field. A mixed-methods research design that relied on surveys and interviews was used to gather data. Alumni employed primarily outside the field held a wide variety of roles and many reported incorporating their musical skills in these roles and they continued to engage in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…If we pay attention to the curriculum of the studies, conservatory graduates feel they lack subjects that respond to various criteria ranging from the need for pedagogical, theoretical-practical or inclusion in the labor market. This question brings to the forefront the debate that is present internationally on curriculum reform (Brook & Fostaty Young, 2019) especially regarding how to adapt to the changing society. Subjects in particular in demand by women and in a statistically significant way are not those most requested by graduates but they can help us to understand specific needs requested by them.…”
Section: Discussionmentioning
confidence: 99%
“…If we pay attention to the curriculum of the studies, conservatory graduates feel they lack subjects that respond to various criteria ranging from the need for pedagogical, theoretical-practical or inclusion in the labor market. This question brings to the forefront the debate that is present internationally on curriculum reform (Brook & Fostaty Young, 2019) especially regarding how to adapt to the changing society. Subjects in particular in demand by women and in a statistically significant way are not those most requested by graduates but they can help us to understand specific needs requested by them.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, this tension may be more observable amongst teachers than amongst the students, who may just care about pursuing higher musical education in order to pursue a musical career rather than purely artistic ideals. Brook and Fostaty Young (2019) found that over 72% of the higher music education alumni they surveyed pursued their studies in HME to prepare for a job in music. Further, given that other empirical research examining the perceptions of musical career identities of 146 music students in the Netherlands revealed that these students do not necessarily experience a tension between entrepreneurial and bohemian "imperatives" (Schediwy et al, 2018, p. 174), it may be particularly interesting to study both this perceived need and conceptualization of entrepreneurship from the perspectives of teachers and administrators whom help comprise the artistic context of HME.…”
Section: Videre Forsknings-og Analysearbeidmentioning
confidence: 99%
“…However, at present, in the curriculum structure and teaching, there are many contradictions and problems in music courses, theory, and practice coordination is insufficient, ignoring the objective needs of the students' music development and employment, resulting in many students can not apply the knowledge they have learned, it is difficult to match with the market demand for jobs. based on this, the music courses of the local colleges and universities are in urgent need of reform and innovation, adjustment and optimization of teaching requirements, and striving to improve the quality of personnel training [4][5][6].…”
Section: Introductionmentioning
confidence: 99%